Linking Microstructural Integrity and Motor Cortex Excitability in Multiple Sclerosis - Radetz, Angela; Mladenova, Kalina; Ciolac, Dumitru; Gonzalez-Escamilla, Gabriel; Fleischer, Vinzenz; Ellwardt, Erik; Krämer, Julia; Bittner, Stefan; Meuth, Sven G.; Muthuraman, Muthuraman; Groppa, Sergiu (Frontiers in Immunology, 2021)
Motor skills are frequently impaired in multiple sclerosis (MS) patients following grey and white matter damage with cortical excitability abnormalities. We applied advanced diffusion imaging for neurite orientation dispersion and density modeling, as well as diffusion tensor imaging (DTI) in 50 MS patients and 49 age-matched healthy controls to quantify microstructural integrity of the motor system. To assess excitability, we determined resting motor thresholds using non-invasive transcranial magnetic stimulation. A hierarchical regression model revealed that lower neurite density index (NDI) in primary motor cortex, suggestive for axonal loss in the grey matter, predicted higher motor thresholds, i.e. reduced excitability in MS patients. Furthermore, lower NDI was indicative of decreased cognitive-motor performance. Motor WM tracts of patients were characterized by overlapping clusters of lowered NDI and DTI-based fractional anisotropy (FA), with NDI exclusively detecting a higher amount of abnormally appearing voxels. Further, orientation dispersion index of motor tracts was increased in patients compared to controls, suggesting a decreased fiber coherence. This study establishes a link between microstructural characteristics and excitability of neural tissue, as well as cognitive-motor performance in multiple sclerosis. We further demonstrate that NODDI parameters are more sensitive measures for quantification of pathological microstructure changes in the WM compared to the classical FA. Our work outlines the potential for microstructure imaging using advanced biophysical models to forecast excitability alterations in neuroinflammation.